Meditation as a Path to Inner Calm in the Life of Buddhists - Adinda Faizah Rahmani; Busro Busro (Subhasita: Journal of Buddhist and Religious Studies, 2023)
The purpose of this research is to find out how to prepare, the form of implementation in Theravada Buddhist meditation, and the most important thing about this research is to find out the psychological condition of Theravada Buddhists who have practiced meditation regularly and correctly. This study uses a qualitative descriptive method, namely research that is directed to conditions and facts that occur in a systematic and accurate manner regarding research and analyzes the truth of these facts based on the data obtained. Data collection techniques in this study used observation techniques, interviews, and a literature study. The discussion is through analysis of the results of observations and interviews. Based on the analysis of the literature and interviews with several sources, Buddhism is teaching contains a lot of ways of life, especially about morality. Meditation, which is one of the teachings of Buddhism, is a path to the final attainment of releasing suffering, and meditation has many benefits for the lives of Buddhists themselves because meditation provides inner peace for those who do it. This meditation requires preparation, such as carrying out moral discipline and also self-control, so that in carrying out this meditation, a person will be able to concentrate. And in the form of practice, this meditation is done by sitting, lying down, standing, and walking. Meditation for Theravada Buddhists is something that must be done in order to attain Nibbana. Followers who regularly meditate will make themselves calm, able to face problems with a cool mind, and most importantly, meditation can also make a person calm by cleaning dirty thoughts from within, where dirty thoughts tend to be negative, and being able to place a position on the present life, not stuck in the past and not expecting a future that has not yet happened. Apart from that, meditation is not only a religious activity, but meditation is also a tool for healing various diseases, which many non-Buddhists can use because they have faith in using this meditation and using the chosen object. This way, our mind will be focused, and mind will not go wild, giving us peace of mind.